2014
DOI: 10.3109/02713683.2014.956371
|View full text |Cite
|
Sign up to set email alerts
|

Topographical Correlation Between Macular Layer Thickness and Clockwise Circumpapillary Retinal Nerve Fiber Layer Sectors in Patients with Normal Tension Glaucoma

Abstract: The identification of these topographical macular areas, and the different layouts in the mRNFL and the mGCL + IPL, may increase the accuracy of clinical research on NTG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…But children are often unable to perform reliable visual fields and it is necessary to search for an alternative surrogate marker for visual loss for both diagnosis and follow-up. Furthermore, it seems that in chronic compressive neuropathies, ganglion cell loss can take place before visual field deficits [ 17 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But children are often unable to perform reliable visual fields and it is necessary to search for an alternative surrogate marker for visual loss for both diagnosis and follow-up. Furthermore, it seems that in chronic compressive neuropathies, ganglion cell loss can take place before visual field deficits [ 17 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yum et al evaluated the detection rate of abnormal colour codes on GCC sector maps in 46 patients with pituitary adenoma; an abnormal yellow colour code was found in the inferonasal sector 34 (73.9%), followed by the superonasal 29 (63.0%) and inferior 29 (63.0%) sectors. Furthermore, analysis of the GCC sector maps revealed that 25% of preperimetric eyes in patients with pituitary adenomas had an abnormal yellow or red colour code in the inferonasal sector [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, SS-OCT has led to significant improvements in the observation of deep areas of the optic nerve head in glaucoma patients [ 12 , 17 , 18 ]. Recently, a new OCT image processing technique has enabled us to assess the axonal tract of the retinal ganglion cells [ 19 ]. In this technique, the curve of the inner limiting membrane (ILM) in OCT B-scan images is flattened through software image correction, and en-face images are then reconstructed from the flattened B-scans.…”
Section: Introductionmentioning
confidence: 99%
“…In this technique, the curve of the inner limiting membrane (ILM) in OCT B-scan images is flattened through software image correction, and en-face images are then reconstructed from the flattened B-scans. In a previous report we used this technique to demonstrate that in patients with glaucoma, visible damage to the macula in SS-OCT images was associated with the anatomical trajectory of nerve fiber defects [ 19 ]. Thus, SS-OCT promises to improve assessment of RNFLDs by allowing the quantification of layer thickness and permitting stable fixation and en face analysis of RNFLDs with SS-OCT has published before [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study measured the correlations between mRNFL thickness (mRNFLT), mGCIPL thickness (mGCIPLT) and cpRNFLT at each point on a grid overlaid on OCT scans of the macula, identified clusters of abnormal points, and then evaluated the potential of these clusters to reveal structural changes in the macula. Previously, we reported that sectors of the macular map could reveal structural changes in eyes with mild or moderate NTG (101 eyes) [ 28 ]. Here, we extended this analysis with a new data set of 117 eyes of 117 cases that included cases of advanced NTG, and identified sectors of the macular map that depended on the axonal tract.…”
Section: Introductionmentioning
confidence: 99%